The Complementary Role of Associations with Public Benefit Status in the Provision of Social Work (Third Sector Social Economic Review, 2025)
The welfare state, both in Turkey and around the world, has entered a period of weakening with neoliberal policies. The growing social problems and the inadequacy of the state in providing social services are also recognised. This means that alternative institutions to the State are becoming increasingly important. In recent years, non-governmental organisations (NGOs) have been seen as supporting the State in providing social services. This study, which examines the social service practices of 364 associations with public benefit status, which are important elements of the non-governmental organisations known as the third sector, aims to highlight the functionality of associations with public benefit status in their social service practices, especially for disadvantaged groups. The study used quantitative content analysis to examine the statutes and websites of non-profit associations and to analyse their social service practices. It has been examined how associations with public benefit status, which are important elements of non-governmental organisations, provide social services to which disadvantaged groups. Consistent with the findings, it was observed that charities focus on services for disadvantaged groups, particularly in areas such as social welfare, psychosocial support, education and employment. In order for associations with non-profit status to carry out their work in the field of social services more effectively, it can be recommended to strengthen the cooperation between the public sector and the third sector and to create public policies that support the third sector.
Keywords: Social Work; Civil Society; Association; Public Benefit